From Bioinspired to Bioinformed: Benefits of Greater Engagement From Biologists - Ng, Leslie; Elgar, Mark A.; Stuart-Fox, Devi (Frontiers in Ecology and Evolution, 2021)
Bioinspiration and biomimetics is a rapidly growing field where insights from biology are used to solve current design challenges. Nature provides an abundance of inspiration to draw upon, yet biological information is under-exploited due to a concerning lack of engagement from biologists. To assess the extent of this problem, we surveyed the current state of the field using the Web of Science database and found that only 41% of publications on bioinspired or biomimetic research included an author affiliated with a biology-related department or organisation. In addition, most publications focus exclusively on a limited range of popular model species. Considering these findings, we highlight key reasons why greater engagement from biologists will enable new and significant insights from natural selection and the diversity of life. Likewise, biologists are missing unique opportunities to study biological phenomena from the perspective of other disciplines, particularly engineering. We discuss the importance of striving towards a bioinformed approach, as current limitations in the field can only be overcome with a greater understanding of the ecological and evolutionary contexts behind each bioinspired/biomimetic solution.